Improving Supplier Delivery Precision Through an OTIF KPI and Root Cause Analysis: A Case Study at Wellspect - Gustafsson, Filip; Turcanu, Christian (My University, 2026)
This study investigates how supplier delivery precision for inbound logistics can be measured and improved through an OTIF KPI. The research was conducted as a case study at Wellspect, a medical technology company, with the aim of increasing the visibility of delivery deviations and improve the supplier performance evaluation. To address the research questions, a qualitative approach was applied, including semi-structured interviews with people across procurement, supply chain, logistics functions as well as analysis of internal data from the company’s ERP system. The findings reveal that the current measurement is structured, but mainly outcome-based, from the compressions between requested delivery dates and goods receipt date. The analysis identifies that NOTIF deliveries are caused by a combination of internal and external factors. Internal causes include planning inaccuracies, inventory- and ERP-issues. External factors include supplier-based deviations and transport disruptions. To address these limitations, an OTIF KPI was developed in a Power BI dashboard. The dashboard improves transparency and enables continuous monitoring by including filtering through order lines, suppliers and delivery terms. The findings emphasize that improving inbound delivery precision requires more than just performance measurement. It also requires improved visibility, internal process alignment and a more differentiated supplier management.
Keywords: inbound logistics, OTIF, supplier performance, Power BI, incoterms, delivery precision, procurement.